Changes in Intraocular Pressure after Transepithelial Photorefractive Keratectomy and Femtosecond Laser In Situ Keratomileusis. (11th March 2021) - Chou, Chien-Chih; Shih, Po-Jen; Lin, Hung-Chou; Chen, Jun-Peng; Yen, Jia-Yush; Wang, I-Jong
Abstract : Purpose . To investigate the changes in intraocular pressure (IOP) and biomechanically corrected IOP (bIOP) in patients undergoing transepithelial photorefractive keratectomy (TPRK) and femtosecond laser in situ keratomileusis (FS-LASIK) and to determine the effects of preoperative biomechanical factors on IOP and bIOP changes after FS-LASIK and TPRK. Design . A retrospective comparative study. Methods . We retrospectively investigated the IOP and corneal biomechanical changes in 93 eyes undergoing FS-LASIK and 104 eyes undergoing TPRK in a clinical setting. Preoperative and postoperative data on ophthalmic and Corvis ST examinations, in vivo Young's modulus, and noncontact tonometry were analyzed. Marginal linear regression models with generalized estimating equations were used for intragroup and intergroup comparisons of IOP and bIOP changes. Results . In the univariate model, IOP reduction after FS-LASIK was 2.49 mmHg higher than that after TPRK. In addition, bIOP reduction after FS-LASIK was 1.85 mmHg higher than that after TPRK. In the multiple regression model, we revealed that IOP reduction after FS-LASIK was 1.75 mmHg higher than that after TPRK. Additionally, bIOP reduction after FS-LASIK was 1.64 mmHg higher than that after TPRK. Postoperative changes in bIOP were less than those in IOP. In addition, Young's modulus and CBI had no significant effect on postoperative IOP and bIOP changes. We establish a biomechanically predictive model using the available data to predict postoperative IOP and bIOP changes after TPRK and FS-LASIK. Conclusions . Reductions in IOP and bIOP after FS-LASIK were 1.75 mmHg and 1.64 mmHg, respectively, more than those after TPRK, after adjustment for confounders. We revealed that the type of refractive surgery and peak distance (PD) were significant predictors of postoperative IOP and bIOP changes. By contrast, depth of ablation showed a significant effect on only IOP changes.